2020
DOI: 10.1111/cen.14190
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of a large cohort of Argentine 21‐hydroxylase Deficiency

Abstract: Context 21‐hydroxylase deficiency is the most common cause of Congenital Adrenal Hyperplasia. It presents as severe or classical forms—salt wasting and simple virilizing—and a mild or nonclassical (NC). Several studies have reported the frequency of pathogenic variants in different populations, although few of them included a large number of NC patients. Objective To analyse the CYP21A2 gene defects in a large cohort of Argentine patients. Design Molecular characterization of 628 patients (168 classical, 460 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Mutational defects in the steroid 21-hydroxylase gene CYP21A2 causing steroid 21-hydroxylase deficiency account for over 90% of CAH cases [ 9 ]. Most genetic defects result from misalignments between the gene and the pseudogene during meiosis that result in deletions, large gene conversions, duplications, or the presence of more than one pathogenic variant in the same allele [ 10 ]. To date, more than 100 CYP21A2 mutations have been reported that are associated either with severe salt-wasting or simple virilizing phenotypes or with milder nonclassical phenotypes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutational defects in the steroid 21-hydroxylase gene CYP21A2 causing steroid 21-hydroxylase deficiency account for over 90% of CAH cases [ 9 ]. Most genetic defects result from misalignments between the gene and the pseudogene during meiosis that result in deletions, large gene conversions, duplications, or the presence of more than one pathogenic variant in the same allele [ 10 ]. To date, more than 100 CYP21A2 mutations have been reported that are associated either with severe salt-wasting or simple virilizing phenotypes or with milder nonclassical phenotypes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%